Penerapan Algoritma Genetika untuk Optimasi Penjadwalan Tebangan Hutan - Ipung Permadi; subanar subanar (JUITA : Jurnal Informatika, 2010)
Scheduling Cuts Away Forest is one of problem met at forestry area. All important problem in finalizing this problem is to determine forest check which will be cut away with a purpose to maximizes yield wood volume in each period cuts away and remain to maintains everlasting forest concept. Method which has been developed to finalize this problem is apply linear program with simplex method. At this method every step is taken based on exact formula is assessed unsatisfying good to finalize this problem. Genetics algorithm is one of alternative of solution of scheduling problems cuts away this forest. This idea of this algorithm comes from the Evolution Theory of Charles Darwin, which is only the best route was choosen. An individual was being choosen from a parent population and then recombined to another individual that has been choosen from another parent population to create a new individu. This new individual expected to be better from the rest individu at the population. With this method, the genetic algorithm found to be able to offer a best Scheduling Cuts Away Forest Problem.